Development and Demographic Parameters of Bactrocera Invadens (Diptera: Tephritidae) in Guinean Climatic Zone of Togo - Gomina, M; Mondedji, A. D; Nyamador, W; Vayssieres, J. F; Amevoin, K; Glitho, A. I (International Journal of Natural Sciences Research, 2014)
Among the 35 Tephritidae species recorded in Togo, only Bactrocera invadens Drew, Tsuruta and White had high prevalence throughout the year and infested fruits of commercial importance. In perspective for control of B. invadens, a wild strain of this pest was reared in an open room conditions similar to those of the external medium (27.5 ± 1 ° C, 79.5 ± 3% RH and approximately 12: 12 L: D). It was fed on local diet consisting of a mixture of soya flour and superfine sugar, and water in the presence of a mango (cultivar Eldon). These conditions allowed us to determine it biological and growth parameters. Ovariole number per ovary in B. invadens was 41. The total mean development time was 21.71 ± 0.99 days. Egg incubation, larval development and puparia-adult periods were respectively 1.28 ± 0.02, 11.35 ± 1.13 and 9.37 ± 0.19 days. About 68.50 ± 5.13% of the eggs developed to the adult stage. Life expectancy at pupal eclosion was 55.03 ± 30.75 days in males and 51.94 ± 21.03 in females. Average fecundity and fertility rates were respectively 535.74 ± 235.70 eggs and 92.67 ± 4.68%. Net reproductive rate and intrinsic rate of population increase were respectively 98.50 females per female and 10% per day. These results summarized the life-history of B. invadens in Guinean zone condition and are useful for assessment of demographic parameters of natural enemies of this insect in perspective of an efficient and sustainable management of its populations.